Aller guten Dinge sind drei: cosmology with three interacting spin-2 fields - Lüben, Marvin; Akrami, Yashar; Amendola, Luca (Arxiv, 2016)
Theories of massive gravity with one or two dynamical metrics generically lack stable and observationally-viable cosmological solutions that are distinguishable from $Λ$CDM. We consider an extension to trimetric gravity, with three interacting spin-2 fields which are not plagued by the Boulware-Deser ghost. We systematically explore every combination with two free parameters in search of background cosmologies that are competitive with $Λ$CDM. For each case we determine whether the expansion history satisfies viability criteria, and whether or not it contains beyond-$Λ$CDM phenomenology. Among the many models we consider, there are only three cases that seem to be both viable and distinguishable from standard cosmology. One of the models has only one free parameter and displays a crossing from above to below the phantom divide. The other two provide scaling behavior, although they contain future singularities that need to be studied in more detail. These models possess interesting features that make them compelling targets for a full comparison to observations of both cosmological expansion history and structure formation.